2022
DOI: 10.1038/s41467-022-28009-0
|View full text |Cite
|
Sign up to set email alerts
|

Absent thermal equilibration on fractional quantum Hall edges over macroscopic scale

Abstract: Two-dimensional topological insulators, and in particular quantum Hall states, are characterized by an insulating bulk and a conducting edge. Fractional states may host both downstream (dictated by the magnetic field) and upstream propagating edge modes, which leads to complex transport behavior. Here, we combine two measurement techniques, local noise thermometry and thermal conductance, to study thermal properties of states with counter-propagating edge modes. We find that, while charge equilibration between… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…Such delta-T noise was recently measured in Ref. [55]. We note also that C (1) vanishes at ∆ T = 1/2 in accordance with Ref.…”
Section: Delta-t Noise In Interacting 1d Systemssupporting
confidence: 92%
See 1 more Smart Citation
“…Such delta-T noise was recently measured in Ref. [55]. We note also that C (1) vanishes at ∆ T = 1/2 in accordance with Ref.…”
Section: Delta-t Noise In Interacting 1d Systemssupporting
confidence: 92%
“…In contrast to the voltage-induced noise, the delta-T noise does not require a net flow of a non-equilibrium charge current. Since initial theoretical [42][43][44][45][46][47][48][49] and experimental [41,[50][51][52][53][54][55] work, it has been shown that non-equilibrium noise in the absence of currents is, in fact, a more general phenomenon than delta-T noise [56]. Still, what properties of nanoscale conductors-and, in particular, facets of their strongly-correlated nature-this class of zerocurrent non-equilibrium noise might reveal, remains an open and interesting question.…”
Section: Introduction a Background And Motivationmentioning
confidence: 99%
“…( 3) requires that L also satisfies L L T , where L T ∼ T −1 is the thermal length. In the intermediate regime L T L H eq , a correction to this value emerges due to backscattering of heat at interfaces with contacts 8,20,25 . For the sake of simplicity, we discard this correction in our analysis in the present work.…”
Section: Methodsmentioning
confidence: 99%
“…1(b,c) for ν = 2/3. While the fullyequilibrated and non-equilibrated limiting cases of G Q have been reported in disparate GaAs/AlGaAs based 2DEG devices 15,16,20 , and in graphene only the non-equilibrated values have been observed 18 , a crossover of G Q from the non-equilibrated to the fully equilibrated limit in a single device has remained unattainable. This has remained one of the long-standing challenges on the path to reveal the detailed edge structure of FQH states.…”
mentioning
confidence: 99%
See 1 more Smart Citation